Applying ANFIS Model in Decision-making of Vertical Handover between Macrocell and Femtocell Integrated Network - Benaatou, Wafa; Latif, Adnane; Pla, Vicent (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2019)
One of the most challenging tasks in communication networks is to maintain seamless mobility and service continuity during a vertical handover. This paper provides the case of handover decision making between femtocell and macrocell integrated network considering several input parameters, namely SINR, bandwidth and energy consumption. We have simulated and proposed a vertical handover based on adaptive neuro-fuzzy inference system (ANFIS) to achieve a goal of having an intelligent handover and to predict the best destination network. The simulation results show that the approach based on ANFIS leads to a reduction of unnecessary handovers and a minimization of the energy consumption as compared to the existing approaches.